Complement component C3 promotes T-cell priming and lung migration to control acute influenza virus infection. - Kopf, M; Abel, B; Gallimore, A; Carroll, M; Bachmann, M (2002)
The complement cascade defines an important link between the innate and the specific immune system. Here we show that mice deficient for the third component of complement (C3-/- mice) are highly susceptible to primary infection with influenza virus. C3-/- mice showed delayed viral clearance and increased viral titers in lung, whereas mice deficient for complement receptors CR1 and CR2 (Cr2-/- mice) cleared the infection normally. Priming of T-helper cells and cytotoxic T cells (CTLs) in lung-draining lymph nodes was reduced, and the recruitment into the lung of virus-specific CD4+ and CD8+ effector T cells producing interferon-gamma was severely impaired in C3-/- but not in Cr2-/- mice. Consequently, T-helper cell-dependent IgG responses were reduced in C3-/- mice but remained intact in Cr2-/- mice. These results demonstrate that complement induces specific immunity by promoting T-cell responses.